Influence of Information and Knowledge towards Attitude in Receiving Vaccines - Lasmery RM Girsang; Ilona Vicenovie Oisina Situmeang; Michael Christian (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
During the pandemic, there are still anxieties among the public, especially those who have not been vaccinated. This condition urges all components like government, public, and media to agree that the essence of the vaccine is a mechanism to control coronavirus spread. This article discusses the application of Information Integration Theory, consisting of (1) valence, which means purpose, in which the information can be positive since the information supports the existing beliefs; and (2) weight of assessment in which the public evaluate the level of source credibility. On quantitative approach, this research statistically tests various tests on all elements. From the 100 samples taken from followers of @kemenkes_ri, the results demonstrate the positive linkage among The Influence of Information (X1), Knowledge (X2), and Attitude (Y). This shows that uploading information about vaccines is needed to provide certainty for followers about the safety and legitimacy of vaccination.